High Intensity Interval Exercise Increases Platelet and Transforming Growth Factor‐β Yield in Platelet‐Rich Plasma. Issue 12 (17th April 2020) - Baria, Michael R.; Miller, Meghan M.; Borchers, James; Desmond, Shannon; Onate, James; Magnussen, Robert; Vasileff, William Kelton; Flanigan, David; Kaeding, Christopher; Durgam, Sushmitha
Abstract : Background: Platelet‐rich plasma (PRP) is an emerging orthobiologic treatment for musculoskeletal conditions like osteoarthritis. Two studies have demonstrated the influence of longer duration exercise on PRP composition, but no study has ever explored the impact of high intensity interval exercise (HIIE) on PRP content. Objective: To quantify cellular and growth factor content changes in PRP after 4 minutes of HIIE. Design: Controlled laboratory pilot study. Setting: Academic sports medicine center. Participants: Ten healthy volunteers (5 male, 5 female). Intervention: Volunteers had PRP prepared from 15 mL of whole blood using a single spin, plasma‐based system (autologous conditioned plasma [ACP]) immediately before and after 4 minutes of HIIE on a stationary exercise bike (Tabata protocol). Main Outcome Measure: The PRP was sent for complete blood counts and enzyme‐linked immunosorbent assay (ELISA) to quantify transforming growth factor (TGF)‐β, platelet‐derived growth factor (PDGF), insulin‐like growth factor (IGF)‐1, and vascular endothelial growth factor (VEGF). Results: Mean platelet count in PRP increased from 367.4 ± 57.5 k/μL to 497.7 ± 93.3 k/μL after 4 minutes of HIIE ( P  < .001). TGF‐β also increased from 8237.2 ± 7676.5 pg/mL to 21 535.7 ± 4062.6 pg/mL postexercise ( P  = .004). The other cellular components (leukocytes, red blood cells, and mean platelet volume) and growth factors (PDGF, IGF‐1, and VEGF) were not significantly changed. Conclusions: A short 4‐minute bout of HIIE significantly increased the total platelet count and TGF‐β concentration in PRP.